The Potential of Public Autonomous Vehicles in Alpine Tourism Destinations - Grèzes-Bürcher, Sandra; Grèzes, Vincent; Fux, Michael; Ramseyer, Randolf; Wilk, Rolf (Téoros)

(untitled) (Université du Québec à Montréal, 2021)
This paper deals with the potential of autonomous public vehicles with an electric power system for alpine tourism destinations. The dilemma of those regions is that they have a high demand for mobility, which is at the same time a risk for their most important assets, such as pure air and tranquillity. This study investigates the opportunities and challenges of public electric autonomous vehicles and focuses on the elements that could hinder a tourism destination from adopting this technology, based on expert interviews. Moreover, it evaluates opinions and concerns of future users of those vehicles. The findings show that public electric autonomous vehicles seem to be a valid solution for alpine tourism destinations that aim to be more sustainable and better aligned with the needs of their tourists. However, those vehicles must be managed in a smart way to avoid an increase in traffic. Technologically, they still need to be improved and be adapted to a challenging alpine environment.